Metronidazole for Treatment of Clostridioides difficile Infections in Brazil: A Single-Center Experience and Risk Factors for Mortality - Joana Darc Freitas Alves; Augusto Yamaguti; João Silva de Mendonça; Cristiano de Melo Gamba; Cibele Lefreve Fonseca; Daniela K. S. Paraskevopoulos; Alexandre Inacio de Paula; Nair Hosino; Silvia Figueiredo Costa; Thaís Guimarães (MDPI AG, 2022)
We describe the epidemiology of C. difficile infections (CDIs) focused on treatment and analyze the risk factors for mortality. This is a retrospective cohort study of CDI cases with a positive A/B toxin in the stool in 2017-2018. We analyzed the demographic data, comorbidities, previous use of antimicrobials, severity, and treatment, and we performed multivariate analysis to predict the 30-days mortality. We analyzed 84 patients, 37 (44%) of which were male, where the mean age was 68.1 years and 83 (99%) had comorbidities. The percentage of positivity of the A/B toxin was 11.6%, and the overall incidence density was 1.78/10,000 patient days. Among the patients, 65.4% had previous use of antimicrobials, with third-generation cephalosporins being the class most prescribed, and 22.6% of cases were severe. Treatment was prescribed for 70 (83.3%) patients, and there was no statistically significant difference between the initial treatment with metronidazole and vancomycin even in severe cases. The 30-day mortality was 7/84 (8.3%), and the risk factors associated with mortality was a severity score ≥2 (OR: 6.0; CI: 1.15-31.1; p = 0.03). In this cohort of CDI-affected patients with comorbidities and cancer, metronidazole was shown to be a good option for treating CDIs, and the severity score was the only independent risk factor for death.